Economic Growth and Environmental Degradation in South Africa: Environmental Kuznets Hypothesis and Sustainable Development - Ogunsola, Akindele John; Zwane, Talent Thebe (International Journal of Energy Economics and Policy, 2026)
This article tests the EKC hypothesis for South Africa from 1990 to 2023 using ecological footprint and biodiversity loss. The paper applies ARDL-ECM, threshold, and quantile regression to establish how green innovation and macroeconomic variables affect environmental sustainability. ARDL results confirm the EKC hypothesis, showing that economic growth initially declines but later improves the environment sustainability. Threshold regression establishes that this only holds when green innovation exceeds a specific threshold. Quantile regression finds that green innovation moderates the environmental effect of exchange rate and trade openness but not GDP, industrial development, or FDI. The paper stresses that environmental improvement is dependent on the size and direction of green innovation. The work calls for coordination between technological progress and macroeconomic policy and suggests investment in green technology, green trade reforms, and directional innovation systems. The study contributes conceptually and methodologically to EKC literature with policy relevance to South Africa.